The Effect of SBI and SBIS as Monetary Instruments on the Indonesian Economy - Isnaini Harahap; Khairina Tambunan (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
As a developing nation, Indonesia uses Gross Domestic Product (GDP) as a measure of economic expansion. To maintain a high GDP, however, it is necessary to address a number of issues, including inflation, interest rates, and exchange rates. In an effort to resolve the issues, monetary operations, including the use of the Bank Indonesia Certificate (Sertifikat Bank Indonesia - SBI) and the Bank Indonesia Sharia Certificate (Sertifikat Bank Indonesia Syariah - SBIS) instruments, were carried out. These instruments should theoretically provide a positive effect on the economy. This study aims to determine the impact of the SBI and SBIS instruments on the economy of Indonesia. Data were obtained in a time series format from the Statistics Indonesia (Badan Pusat Statistik - BPS) and Bank Indonesia websites. It was interpolated on a monthly basis and analyzed using the VAR VECM method to determine short-term and long-term effects. The findings show that the SBIS variable has a significant impact on economic growth, whereas the SBI has no effect on the Indonesian economy. This result suggests that the Indonesian monetary authorities should consider using SBIS as a tool to support economic growth rather than SBI.==========================================================================================================ABSTRAK – Pengaruh SBI dan SBIS Sebagai Instrumen Moneter terhadap Ekonomi Indonesia. Indonesia sebagai negara berkembang menjadikan Produk Domestik Bruto (PDB) sebagai indikator pertumbuhan ekonomi. Namun untuk mempertahankan PDB yang tinggi, terdapat beberapa masalah diantaranya inflasi, suku bunga maupun nilai tukar. Untuk mengatasi persoalan tersebut secara moneter, dilakukan operasi moneter diantaranya dengan menggunakan instrument SBI dan SBI. Secara teoritis, kedua instrument harus memberikan dampak positif terhadap pertumbuhan ekonomi. Karenanya penelitian ini bertujuan untuk mengetahui dampak instrument SBI dan SBIS terhadap perekonomian Indonesia. Data penelitian dikumpulkan dalam bentuk time series dari situs BPS dan BI. Data tersebut diinterpolasi secara bulanan dan dianalisis dengan metode VAR VECM untuk menemukan dampak SBI dan SBIS pada periode jangka pendek dan jangka panjang. Hasil penelitian menunjukkan adanya dampak yang signifikan variabel SBIS terhadap pertumbuhan ekonomi, sementara SBI tidak berdampak signifikan terhadap perekonomian Indonesia. Implikasi temuan ini adalah otoritas moneter harus lebih mempertimbangkan SBIS dibandingkan SBI sebagai instrumen operasi moneter guna mendukung pertumbuhan ekonomi.